Demystifying Educational Demands: Analyzing the Needs for the Online Comprehensive Test Application at Islamic University - Andi Harpeni Dewantara; Muh. Syahrul Sarea (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to identify the needs for developing an online comprehensive test application at one of the Islamic universities in Indonesia. The needs assessment includes target situation analysis, user needs analysis, reality analysis, and gap analysis. This is a descriptive quantitative research involving 135 examiners and students who are taking comprehensive examinations from all four faculties at IAIN Bone as samples. Sampling technique used a stratified random sampling. Questionnaires and interview techniques were utilized for data collection, followed by a descriptive analysis. The findings reveal several weaknesses in the comprehensive test system. These include the lack of integration among all faculties, partial implementation, a highly flexible exam schedule, a paper-based test administration method, a lack of standardized instrument development, and suboptimal utilization of comprehensive test results for mapping student competencies. To conclude, it is necessary to develop an online comprehensive test application which is expected to be able to make the implementation of the comprehensive test at IAIN Bone more integrated, programmed, and effective. Keywords: Need Analysis, Online Comprehensive Test, Online-Based Assessment